Assesment of Cholera Preventive Practices Among Residents of Samaru Community, Sabon-Gari, Kaduna State, Nigeria - Abdulmuhit Temitope ISIAQ; Seun Nurudeen AKOREDE; Adam Abiola AKOREDE (Unnes Journal of Public Health, 2023)
Throughout the years, cholera outbreaks have plagued many different countries. Cholera is not only a problem from the past; it's still a big public health issue today. This study assessed the cholera prevention practices among residents of Samaru Community, Sabon-gari, Kaduna State, Nigeria. The ex-post facto research design was used. A sample size of three hundred and seventy-six (376) respondents was conveniently drawn from a population of 18,039 residents of Samaru Community, Sabongari, Kaduna State, Nigeria. A researcher-developed close-ended questionnaire was used to obtain responses from the participants. Descriptive statistics of frequency, percentages, means and standard deviations were used to answer the research question and inferential statistic of one-sampled t-test was used to test the stipulated hypothesis at 0.05 level of significance. The findings of the study revealed that the cholera prevention practice is significant (t=5.652; p= 0.000). Based on the findings of the study, it was concluded that residents of Samaru Community, Sabongari, Kaduna State practice cholera prevention strategies. The study recommended the need for awareness campaigns through health talks to assist sustain the already existing cholera preventive practices among the population of Samaru community, Sabongari Local Government Area, Kaduna State, Nigeria.